AUDITORY REPETITION PRIMING FOR ENGLISH WORD STRESS APPLYING AUDITORY PRIMING IN TEACHING ENGLISH WORD STRESS - Clara Herlina Karjo (Indonesian JELT, 2012)
This paper discusses the implications of using the auditory priming method in teaching English word stress to Indonesian university students. In auditory priming experiment, 30 participants had to pronounce 80 English words after hearing the stimuli (i.e. prerecorded 80 words with correct stress placement). The data was taken from the recordings of the students’ responses, which were transcribed carefully to determine the stress placement. Research revealed that auditory priming effect was achieved although the result was not statistically significant. The result of this study was significant for Indonesian EFL teachers as it give insight for the implementation of the auditory priming method to teach English pronunciation.Keywords : Auditory priming, word stress placement,priming effect